Diabetes mellitus hospitalization and mortality rate according to a national database in Brazil: a longitudinal study - Florêncio, Rêncio Bento (BMC Public Health, 2021)
BACKGROUND: Diabetes mellitus (DM) is an important public health problem worldwide. In addition to the impairment in functionality, the large number of complications which lead to hospitalizations results in high treatment costs. The aim of this study was to analyze the incidence of hospitalizations, mortality rate and hospital costs, as well as to observe the temporal trend of hospitalizations and length of hospital stay due to DM between 2008 and 2019 in Brazil. METHODS: This is a longitudinal descriptive study in which all data regarding hospital admissions registered in the Brazilian system of Hospital Information of “Sistema Único de Saúde” (SIH/SUS; http://datasus.saude.gov.br) due to DM (ICD-10) were included. Comparisons among the groups were performed by an unpaired Student’s t-test, two-way ANOVA with a Tukey post hoc test (p < 0.05). RESULTS: An increased hospitalization of 1.83% due to DM was observed between 2008 and 2019 in Brazil. The Southeastern region had the highest incidence (34.6%) and mortality rate when compared to the other regions (p < 0.05). We also found that females were more likely to be hospitalized in comparison to males, without a statistically significant difference. Finally, a progressive increase of hospitalizations and mortality rate were observed according to age groups, as well as increased spending due to DM hospitalizations over the years. CONCLUSION: Hospitalizations due to DM in Brazil showed an expressive increase over the last 12 years, and there is a need for primary healthcare interventions to help reduce this situation.